A cultura participativa na educação: superando a perspectiva instrumental no uso dos mecanismos de comunicação digital nos sistemas básico e médio de ensino - Odainai, Alexandre Alves Sinfronio (2013)
The aim of this dissertation is to make a reflection on the way to prepare young students from primary and secondary school in a participatory culture where according to Henry Jenkins popular participation supported by the Internet has expanded the possibilities of interference in society. This active collaboration caused profound changes in sensitive contemporary aspects such as intellectual property, the diversification of cultural expression, the development of skills valued in the modern workplace, and a more empowered conception of citizenship. However, it is necessary to reflect on what Jenkins celebrates as participatory culture since this concept is immersed in an order of dromocratic exclusion where the mercantile logic guides the use and the language of media technologies as noted by Trivinho and Orozco-Gomez. Taking into account the prevalence of new technologies in educational and communication field, it becomes essential to criticize the specific modes of technology incorporation within the school system. The hypothesis presented to answer this problem suggests that these various conditions depend on a number of environmental and internal factors to the system, overcoming the illusory idea that only restricted access to the new media technologies is enough. It is required an axiological dimension that involves values and affection. The adopted methodology is based fundamentally on bibliographical research guided by analysis of the paper Confronting the Challenges of Participatory Culture: Media Education for the 21st Century by Henry Jenkins. The argument structure is divided into: 1) From Individualism to Cooperation 2) Participatory Culture 3) Overcoming the Participatory Culture. The theoretical frame of reference is composed by authors such as Dewey, Maturana Romesín, Franco, Orozco-Gomez, Trivinho, Castells and Ugarte and it is based on the perspectives of Systems Theory, Cultural Biology, Cyberculture Studies, Dromology Studies and Mediatic Civilization